Adverse Reactions to Injectable Fillers - Fitzgerald, Rebecca; Bertucci, Vince; Sykes, Jonathan M.; Duplechain, J. Kevin (Facial Plastic Surgery, 2016)
As the use of fillers becomes increasingly more common and the skill level of those injecting is so varied, adverse events can be expected to increase as well. Avoiding complications is always the best measure, and with appropriate training and injection techniques, many complications can be avoided. However, adverse events can occur in the best of hands, and early detection and treatment may eliminate or minimize sequelae. This article is an effort to help in that endeavor.
Keywords: fillers; complications; adverse events; biofilm; intravascular injection; ischemia; necrosis